A review on markov models and web page prediction (International Journal of Engineering and Computer Science, 2015)
A Markov process is a stochastic process in which the probability distribution of the current state is conditionally independent of the path of past states, a characteristic called the Markov property. Markov chain is a discrete-time stochastic process with the Markov property. In this paper we have to use the Markov model for the prediction of the different web pages based on the sequence of previously accessed page